Potensi Energi Pirolisis Sampah Plastik Polypropylene (PP), Polystyrene (PS), dan High-Density Polyethylene (HDPE) Berdasarkan Nilai Kalor - Suri, Wiranda Intan; Ratnawati, Beata; Paramitadevi, Yudith Vega; Tunggadewi, Andini Tribuana; Prasetya, Dimas Ardi; Wahdi, Emil (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2026)
Indonesia, as a country with a high population and rapid industrialization, produces a very large amount of plastic waste every year. The application of pyrolysis technology can be used as an alternative solution to convert plastic waste into an energy source in the form of pyrolysis oil. The study aims to analyze the energy potential of pyrolysis oil products from plastic waste types Polypropylene (PP), Polystyrene (PS), and High-Density Polyethylene (HDPE) based on their calorific value and evaluate the potential of oil to be used as an alternative fuel by comparing the calorific value with conventional fuels such as gasoline, diesel, and kerosene. The pyrolysis process was carried out on each type of plastic waste, and then the oil was tested for its Gross Calorific Value (GCV) using the Bomb Calorimeter method. The results showed that the pyrolysis oil from the three types of plastic waste had a high calorific value (GCV), 46.27 MJ/kg for PP, 44.27 MJ/kg for PS, and 45.16 MJ/kg for HDPE. All three types of plastic waste have great potential to be used as alternative fuels. The oil from the pyrolysis of PP plastic waste has the highest calorific value, so based on the calorific value, the pyrolysis oil from PP plastic waste has greater energy potential compared to PS and HDPE plastic waste.